Dukungan keluarga dan kemandirian pasien dengan gangguan jiwa yang menjalani perawatan di Yayasan Aulia Rahma - Teguh Pribadi; Sumartono Sumartono (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2022)
Background: Mental health or mental health is a state of complete physical, mental and social well-being, and not only free from disease, disability, and infirmity, which enables a person to live productively, both socially and economically. Data from the Lampung Provincial Hospital in 2021, the number of patients with Mental Disorders with mental disorders was 20,416 patients and 15,578 people (77.3 percent) had mental disorders and the total number of patients was the number of patients in the category of 10 cases or the most types of diseases being treated. at the Regional Hospital of Province Lampung. Purpose: To know relationship between family support and independence behavior among patients with mental disorders at Yayasan Aulia Rahma. Method: This type of research is quantitative, analytical design with a cross-sectional approach. The population in this study were all families of mental patients who underwent treatment at the yayasan Aulia Rahma on November 2020. The sampling technique used accidental sampling, where 46 respondents were obtained when the family came to visiting, and a questionnaire would be given. The family support instrument uses a questionnaire of 20 statements. Meanwhile, to see the patient's independence by using the observation sheet after the patient underwent 60 days of treatment and his condition had recovered, which was accompanied by regularity in taking medication and activities and being able to control symptoms. The independence observed included 10 items, such as self-care initiatives, independence in tidying and cleaning the correct bed, and cleanliness of the room and its environment. Data analysis using chi-square test. Results: Family support was obtained in the majority of mental patients with mental disorders in the low support category of 72.0 percent. The level of independence of patients with mental disorders is still at a low level at 67.3 percent. Conclusion: There is a relationship between family support and the independence of mental patients with mental disorders (p-value = 0.003 < 0.05). Suggestion: The management of the foundation to socialize the form of support to the patient's family to always provide support, so that the patient can recover quickly and learn independently so that he can be immediately discharged. Keywords: Family Support; Independence; Patients; Mental disorders. Pendahuluan: Kesehatan mental atau kesehatan jiwa merupakan keadaan sejahtera yang lengkap dari fisik, mental dan sosial, dan bukan hanya bebas dari penyakit, cacat dan kelemahan, yang memungkinkan seseorang hidup produktif, baik secara sosial, maupun ekonomis. Data RSJ Provinsi Lampung tahun 2021 jumlah penderita dengan Gangguan Jiwa (ODGJ) gangguan jiwa sebesar 20.416 pasien dan sebesar 15.578 orang (77,3 persen) mengalami gangguan jiwa dan total pasien tersebut merupakan jumlah pasien yang masuk kategori 10 kasus atau jenis penyakit terbanyak yang ditangani di RSJ Daerah provinsi Lampung. Tujuan: Diketahui hubungan dukungan keluarga dan kemandirian pasien dengan gangguan jiwa yang menjalani perawatan di Yayasan Aulia Rahma Metode: Jenis penelitian kuantitatif, desain analitik dengan pendekatan cross sectional. Populasi dalam penelitian ini adalah seluruh keluarga pasien gangguan jiwa yang menjalani perawatan di Yayasan Aulia Rahma di bulan November 2020. Teknik sampling menggunakan accidental sampling didapatkan sebanyak 46 responden dimana saat keluarga datang berkunjung maka akan diberikan kuesioner. Instrumen dukungan keluarga menggunakan kuesioner sebanyak 20 pernyataan. Sedangkan untuk melihat kemandirian pasien dengan menggunakan lembar observasi setelah pasien menjalani 60 hari perawatan dan kondisinya sudah pulih, yang disertai keteraturan makan obat dan aktivitas serta mampu mengendalikan gejala. Kemandirian yang di observasi meliputi 10 item, seperti inisiatif perawatan diri, kemandirian dalam merapikan dan membersihkan tempat tidur yang benar serta kebersihan kamar dan lingkungannya. Analisis data menggunakan uji chi square. Hasil: Didapat dukungan keluarga pada pasien jiwa gangguan jiwa mayoritas pada kategori dukungan rendah sebesar 72.0 persen. Tingkat kemandirian pasien gangguan jiwa masih dalam tingkat rendah pada sebesar 67.3 persen. Simpulan: Ada hubungan dukungan keluarga dengan kemandirian pasien jiwa gangguan jiwa (p value = 0,003 < 0,05). Saran: Manajemen yayasan untuk mensosialisasikan bentuk dukungan kepada keluarga pasien untuk selalu memberikan dukungannya, sehingga pasien dapat segera pulih dan belajar mandiri sehingga dapat segera dipulangkan.